2017
DOI: 10.1080/02640414.2017.1331042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drop sets with resistance training on increases in muscle CSA, strength, and endurance: a pilot study

Abstract: To investigate the effects of a single high-load (80% of one repetition maximum [1RM]) set with additional drop sets descending to a low-load (30% 1RM) without recovery intervals on muscle strength, endurance, and size in untrained young men. Nine untrained young men performed dumbbell curls to concentric failure 2-3 days per week for 8 weeks. Each arm was randomly assigned to one of the following three conditions: 3 sets of high-load (HL, 80% 1RM) resistance exercise, 3 sets of low-load [LL, 30% 1RM] resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 19 publications
1
68
2
Order By: Relevance
“…Regarding the assessments, muscle hypertrophy was assessed for the lower limbs in 15 studies ( 3 – 7 , 32 , 35 39 , 43 , 44 , 49 , 50 ), followed by 8 studies assessing the upper limbs ( 4 , 7 , 32 , 34 , 45 , 47 , 48 , 50 ) and 5 studies assessing the whole body (e.g., dual-energy x-ray absorptiometry) ( 33 , 40 , 42 , 46 , 53 ), whereas lower-body muscle strength was assessed in 20 studies ( 3 – 7 , 32 , 33 , 35 , 38 44 , 46 , 48 , 50 52 ), followed by 12 studies assessing upper-body muscle strength ( 2 , 4 , 7 , 33 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 51 ), all using the 1-RM test. Eighteen studies reported the total volume performed during the intervention ( 4 , 5 , 7 , 32 35 , 37 45 , 48 , 50 ). The number of studies among the resistance training loads for muscle hypertrophy and muscle strength is shown in the network geometry (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the assessments, muscle hypertrophy was assessed for the lower limbs in 15 studies ( 3 – 7 , 32 , 35 39 , 43 , 44 , 49 , 50 ), followed by 8 studies assessing the upper limbs ( 4 , 7 , 32 , 34 , 45 , 47 , 48 , 50 ) and 5 studies assessing the whole body (e.g., dual-energy x-ray absorptiometry) ( 33 , 40 , 42 , 46 , 53 ), whereas lower-body muscle strength was assessed in 20 studies ( 3 – 7 , 32 , 33 , 35 , 38 44 , 46 , 48 , 50 52 ), followed by 12 studies assessing upper-body muscle strength ( 2 , 4 , 7 , 33 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 51 ), all using the 1-RM test. Eighteen studies reported the total volume performed during the intervention ( 4 , 5 , 7 , 32 35 , 37 45 , 48 , 50 ). The number of studies among the resistance training loads for muscle hypertrophy and muscle strength is shown in the network geometry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Third, although recreationally trained participants were included in our analyses, the strength levels reported in the studies were relatively modest, and certainly, the present results cannot be extrapolated for highly strength-trained individuals (e.g., bodybuilders, collegiate athletes in structured and supervised strength and conditioning programs, and power or strength athletes). Fourth, several studies ( 4 , 5 , 33 , 37 , 38 , 43 45 , 50 , 52 ) have performed multiple 1-RM testing throughout the study duration (range, 3–5 times). This may also be considered an issue masking an even greater difference between low- versus moderate- and high-load resistance training programs because of the number of exposures to maximal strength tests and the potential increases in muscle strength not related to the intervention per se ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests the beneficial effects of both drop sets and SST in acute increases in triceps brachii muscle thickness [53] in both amateur and well-trained subjects, even with lower training volume versus a traditional set scheme RT. However, studies that have investigated the chronic effects of drop sets did not show a superior hypertrophy response when compared with traditional sets [52,54]. Moreover, the chronic effects of SST on muscle growth have not been examined yet.…”
Section: Drop Sets and Sarcoplasma Stimulating Training Techniquementioning
confidence: 99%
“…For example, Angleri et al [10] compared the effects of the traditional, pyramid, and drop-set techniques with equal-ized total volume-load in trained men, and observed similar hypertrophy for the three groups. In the same way, Ozaki et al [11] observed similar hypertrophy for the elbow flexors between drop-set and traditional groups after eight weeks of training in untrained young men; in parallel, volume-load was also similar between them. Regarding the rest-pause, Prestes et al [12], also in an experimental design of volume equalized with the traditional RT protocol, observed similar changes in lean mass, and muscle thickness of biceps brachii and pectoralis major, in trained young adults; although anterior mid-thigh hypertrophy was greater for the rest-pause group.…”
Section: Argumentationmentioning
confidence: 61%
“…In this scenario, the objectives of this manuscript were 1) to present the nuance of the evidence that deals with the effectiveness of these specialized resistance training techniques and -primarily -to 2) propose possible ways to explore the hypertrophic potential of such strategies with greater ecological validity without losing the methodological rigor of controlling possible intervening variables; and thus, contributing to increasing the applicability of the findings and improving the effectiveness of hypertrophy-oriented resistance training programs. associated with differences in volume between groups [10][11][12]. While this is a valid scientific approach, it minimizes the ecological validity to training rooms, since the possible advantages that justify the application of these techniques (e.g., make a larger volume) are not explored.…”
Section: Introductionmentioning
confidence: 99%